FACTORIAL STRUCTURE OF THE MORPHOLOGICAL STATUS OF FEMALE CADET HANDBALL PLAYERS - Miroljub Ivanović; Uglješa Ivanović (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to determine the constitution and the latent structures on the sample of 124 female handball players, age 13.72 (SD = 5.16). The measuring instruments of this transversal research included the set of 12 anthropometric variables (Mišigoj-Duraković, 1995). The descriptive methods with the statistical significance of p ≤ .05, as well as exploratory factor analysis (EFA), along with the Guttman-Kaiser Criterion for reducing the number of main components using the oblimin rotation of variables were used in the data processing. The obtained results revealed the existence of the relevant four-factor hierarchical model, with 71,44% of the explained variance. The first most informative latent dimension was interpreted as the factor of longitudinal dimensionality of the skeleton (explained 37.02% of the variability), the second was subcutaneous fat (20.25% of the variability), the third is was body mass and volume (7.86% of the variability), and the forth was transversal dimensionality of the skeleton (6.31% of the explained variability). The factorial findings confirmed the hypothetical morphological structure of the extracted mutual factors of the participants, which is in accordance with the results of other researches. This study revealed practical implications and methodological limitations of this empirical research, and thus included recommendations for future research.